PENGARUH LOKASI DAN LAMA USAHA TERHADAP PENDAPATAN PEDAGANG DI PASAR CIBINONG KABUPATEN BOGOR - Wawan Hari Subagyo; Benny Osta Nababan; Mujito Mujito; Novia Dwi Jayanti (Institut Teknologi dan Bisnis Dewantara, 2023)
This study was conducted to determine the effect of business location and length of business on the income of traders in Cibinong Market, Bogor Regency. The results of the study proved that: (1) The results of the hypothesis test partially proved that business location affected the income of traders in Cibinong Market, Bogor Regency, this was shown by the value of t calculating the variable business location of 2.625 > t table 1.660 with a significance value of 0.010 < 0.10. (2) The results of the hypothesis test partially prove that the length of business affects the income of traders in Cibinong Market, Bogor Regency, this is shown by the value of t calculate the variable business location of 3.484> t table 1.660 with a significance value of 0.001 < 0.10. (3) The results of the hypothesis test simultaneously prove that the location of the business and the length of business simultaneously affect the income of traders in Cibinong Market, Bogor Regency, This is indicated by the calculated t value of the business location variable of 62.794 > 2.001 with a significance value of 0.000 < 0.10. (4) The most dominant variable affecting business income is the length of business variable, this can be seen from the value of the regression coefficient of the brand image variable of 0.546.